DISPARITAS PUTUSAN HAKIM DALAM PERKARA PERBUATAN MELAWAN HUKUM TERHADAP PEMBATALAN PERJANJIAN SEWA-MENYEWA SECARA SEPIHAK - Nur Hidayatullah; Nur Arifudin; Amsari Damanik (INTELIGENSIA MEDIA, 2024)
Unilateral cancellation of the agreement before the end of the agreement period is categorized as unlawful. In some cases of unilateral cancellation of lease agreements submitted to the District Court, there are differences in legal considerations by the Panel of Judges in interpreting elements of unlawful acts in unilaterally canceling agreements resulting in disparity in decisions. The research method used is doctrinal research based on a legal issue that is examined in several District Court decisions with a statutory approach and relevant legal theories. The results showed that the disparity in judges' decisions in Decision Number 760/Pdt.G/2017/PN.Dps, Decision Number 404/Pdt.G/2019/PN.Bdg, and Decision Number 196/Pdt.G/2020/PN. Jkt.Sel in its legal consideration, the Panel of Judges considered that not all unilateral cancellation of agreements can be categorized as unlawful acts based on certain things that prove that there is strong evidence and clear reasons for one party to cancel the lease agreement unilaterally. Efforts to minimize the disparity of the three decisions are the establishment of a more specific agreement clause that regulates provisions related to matters that cause the cancellation of the lease agreement, the Panel of Judges is more optimal in assessing the facts revealed in the trial, the use of jurisprudence and improving guidance and evaluation for judges by the Supreme Court.